2014
DOI: 10.1074/jbc.m113.476861
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Communication between Agonist and Coactivator Binding in the Retinoid X Receptor α Ligand Binding Domain

Abstract: Background: Some retinoid X receptor (RXR) agonists have potential as cancer drugs. Results: Structures of RXR in complex with two different agonists show similar folds. Dynamics analysis reveals unique ligand-induced dynamics in helices 3, 11, and 12. Conclusion: Two networks of interactions that connect RXR agonists to coactivator binding are defined. Significance: Recognition of common conformational changes and distinguishing dynamics of RXR-selective agonists is necessary for advances in drug design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
102
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(109 citation statements)
references
References 62 publications
7
102
0
Order By: Relevance
“…1, 2, 10 Here crystal strutures of hRXRα-LBD homodimers containing the coactivator peptide GRIP-1 with one of four potent agonists ( 6 , 9, 10 and 11 ) were obtained and compared. Crystals of the homodimer containing the partial agonists, 8 or 12 , were not successfully obtained after repeated tries using similar conditions of crystallization to those of full agonists.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1, 2, 10 Here crystal strutures of hRXRα-LBD homodimers containing the coactivator peptide GRIP-1 with one of four potent agonists ( 6 , 9, 10 and 11 ) were obtained and compared. Crystals of the homodimer containing the partial agonists, 8 or 12 , were not successfully obtained after repeated tries using similar conditions of crystallization to those of full agonists.…”
Section: Resultsmentioning
confidence: 99%
“…Each rexinoid adopts an L-shaped conformation, which is characteristic of the way rexinoid agonists or the pan-agonist 9-cis-retinoic acid bind to the receptor. 1, 2 The binding of the rexinoid agonists cause similar, but not identical, conformational and dynamical changes to the ligand binding domain enabling the recruitment of an amphipathic coactivator peptide containing the LL xx LL motif. Each rexinoid reduces proliferation and enhances apoptosis in mammary tumors, and efficiently prevents mammary cancers in rodent models.…”
Section: Introductionmentioning
confidence: 99%
“…19 The rate of hydrogen/deuterium exchange of backbone amide hydrogens reflects the conformational mobility, hydrogen bonding strength, and solvent accessibility in the protein structure. 20 In fact, the in-solution 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 5 dynamics of several NRs, including VDR, have been investigated using HDX-MS. [23][24][25][26][27][28][29][30][31][32][33] To develop strong antagonists and to reveal the mechanism of active antagonism of the VDR, we designed and synthesized vitamin D analogues with bulky substituents at the side chain terminus and used them to probe changes in the VDR-LBD structure upon binding to synthetic active antagonists. Here, we report the synthesis and biological evaluation of compounds 2a,b-6a,b ( Figure 1) and the results of static X-ray crystallographic and dynamic HDX-MS analyses of the VDR-LBD/antagonist complex.…”
Section: Introductionmentioning
confidence: 99%
“…In the X-ray crystal structure of hRXRα-LBD homodimers bound to 9cUAB30 with the coactivator peptide GRIP-1, we revealed that the binding pocket contained enough space to accommodate a small lipophilic group on the tetralone ring. 10 Methyl substitution has proven to be very effective in improving activity through lipophilic interactions and/or from energetic gains realized by burial of the methyl group in the hydrophobic pockets of the protein. 11 Racemic 1 ((±)- 1 ) possesses a methyl group at the 4-position of the tetralone ring, and it is also known as 4-methyl-9c-UAB30 in the literature (Figure 1).…”
Section: Introductionmentioning
confidence: 99%